The Role of Renewable Energies for the Sustainable Energy Governance and Environmental Policies for the Mitigation of Climate Change in Ecuador - Flavio R. Arroyo M. (Energies, 2020)
This article presents a comparative analysis of energy governance with respect to renewable energy sources in Ecuador. The use of renewable energy sources increases energy security and enables countries to achieve their climate mitigation goals. Ecuador’s energy mix is dominated using fossil fuels and produces only 7.8% of its energy supply from renewable energy. The scenario analysis suggests that using the example of international renewable energy policies will achieve sustainable energy development in Ecuador. Relying less on fossil fuels and decentralizing the electricity sector from the use of thermoelectric plants is the great challenge for the country. Using the enormous water potential that Ecuador has and taking advantage of the sources of solar, biomass and wind energy available in the country will reduce the forecast of 60,233.70 KT CO2 by 2030 that would be reached if current consumption conditions and energy mix are maintained, while designing a long-term energy planning with a greater participation of renewable energies would forecast a CO2 emission of 41,232.30 KT, that is, a reduction of 31.5% in emissions.